Transformation in the national department of public works: a market driven strategy - S , Mahadeo; S, Davids; N, Nair (2008)

(untitled)
This paper investigates the depth and extent to which the National Department of Public Works NDPW) is transforming within the Built Environment, relative to the social, economic, political, historical, gender, legal and equity spheres. Transformation is one of the most critical aspects of effective strategic management and the South African government, through the (NDPW), is committed to facilitating delivery by other departments by providing accommodation and property management services and meeting the objectives of poverty alleviation and transformation. In 2003 the Department formulated a new vision, mission and value statements to demonstrate the Department’s and its employees’ serious commitment to Government’s vision of a better life for all the country’s citizens. The (NDPW) aims to promote the government’s objectives of economic development, good governance and rising living standards and prosperity by providing and managing the accommodation, housing, land and infrastructure needs of national departments, by promoting the national Expanded Public Works Programme and by encouraging the transformation of the construction and property industries. In pursuance of this objective the Department will endeavour to efficiently manage the asset life cycle of immovable assets under the Department’s custodianship, provide expert advice to all three spheres of Government and parastatals on immovable assets, contribute to the national goals of job creation and poverty alleviation through the coordination of public works programmes nationally, of which the Expanded Public Works Programme (EPWP) and National Youth Service (NYS) forms an integral part; and provides strategic leadership to the Construction and Property Industries.